Lumbar spinal stenosis and surgical decompression affect sleep quality and position in patients. A prospective cross-sectional cohort study - Luca Papavero; Jana Wilke; Nawar Ali; Kathrin Schawjinski; Annette Holtdirk; Karsten Schoeller (Brain and Spine)
Introduction: It is reasonable to assume that lumbar spinal stenosis (LSS) affects the cauda nerve roots also at night. Research question: Does microsurgical decompression influence sleep quality and position? Materials and methods: A study nurse interviewed 140 patients scheduled for LSS decompression using the Pittsburgh Sleep Quality Index (PSQI), Spinal Stenosis Measure (SSM), Numeric Rating Scale (NRS) for back and leg pain, Douleur Neuropathique (DN4), and Charlson Comorbidity Index. Epidemiologic and MRI data were collected along with self-reported rankings of preferred sleep positions (prone, supine, side, and fetal). Follow-up interviews were conducted by telephone six and 18 months after discharge. Statistical analysis was performed using SSPS 24, with significance set at p < 0.05. Results: 132 patients (55% female, mean age 73 years) were evaluated. Preoperatively, 45 (34.1%) patients were classified as good sleepers (GS: PSQI ≤5, range 1–21 (worst)) and 87 (65.9%) as poor sleepers (PS: PSQI ≥6). Decompression surgery reversed the relationship between PS (31.8%) and GS (68.2%, recovered/improved). Protective fetal sleeping position was the most common (≥70%) before and after surgery for both PS and GS. Risk factors for PS included female sex (p = 0.03), obesity (p = 0.03), high NRS back pain score (p = 0.008), and high SSM symptom score (p = 0.004). MRI imaging did not differ between PS and GS. Discussion and conclusion: LSS had a negative effect on sleep quality, whereas surgical decompression had a positive effect. The protective fetal sleeping position was the preferred position both before and after surgery.